Wake - Burr, Shelley (Sydney, NSW : Hachette Australia, 2022)
"Evelyn simply vanished. The small town of Nannine lies in the harsh red interior of New South Wales. Once a thriving outback centre, years of punishing drought have whittled it down to no more than a couple of pubs and a police station. And its one sinister claim to fame: the still-unsolved disappearance of Evelyn McCreery nineteen years ago from the bedroom she shared with her twin sister. Mina McCreery's life has been defined by the intense and ongoing public interest in her sister's case. Now an anxious and reclusive adult, Mina lives alone on her family's sunbaked destocked sheep farm. The million-dollar reward her mother established to solve the disappearance has never been paid out. Enter Lane Holland, a private investigator who dropped out of the police academy to earn a living cracking cold cases. Lane has his eye on the unclaimed money, but he also has darker motivations for wanting to solve the case."--Back cover.
"No forced entry. No fingerprints. No footprints. No tyre marks. What really happened to young Evie McCreery?"--Cover.
CWA Debut Dagger, 2019
Keywords: Sisters -- Fiction; Missing persons -- Fiction; Missing persons -- Investigation -- Australia -- Fiction; Cold cases (Criminal investigation) -- Fiction; Private investigators -- Australia -- Fiction; Rewards programs (Criminal investigation) -- Fiction; Country life -- New South Wales -- Fiction; Australian fiction; New South Wales -- Fiction; Australian; Detective and mystery fiction